Factors Related to Nurses’ Attitudes Toward the Elderly Care: The Predictive Roles of Altruism, Moral Intelligence, Life Satisfaction and General Health - Mostafa Rad; Neda Mahdavifar; Raha Salehabadi; Maryam Ghorbani (Sālmand, 2021)
Objectives: Nurses’ attitudes affect their preference for caring for the elderly as well as the quality of care. This study aims to investigate the factors related to nurses’ attitudes toward the elderly care and assess the predictive roles of altruism, moral intelligence, life satisfaction and general health. Methods & Materials: This descriptive-analytical study with a cross-sectional design was conducted on 265 nurses working in hospitals in Sabzevar, Iran in 2019. Data were collected using a demographic form, Kogan’s Attitudes Toward Old People Scale,Lennick and Kiel’s Moral Competency Inventory, Carlo’s revised form of Prosocial Tendencies Measure, Diener’s Satisfaction With Life Scale , and General Health Questionnaire-28 item. Data were analyzed using descriptive statistics (mean, standard deviation, and frequency) and inferential statistics (Pearson correlation test, linear regression analysis, and independent t-test) in SPSS v. 16 software. The significance level was set at 0.05. Results: The Mean±SD age of participants was 33.10±7.17 years. Nurses had a positive attitude toward the elderly care. Their Mean±SD attitude score was 155.39±17.74. There was no significant relationship between nurses’ attitudes and variables of age, gender, marital status, education, work experience, ward, and general health (P>0.05). The multiple regression model showed that the factors of moral intelligence (P=0.01), altruism (P=0.008) and life satisfaction (P=0.03) had a significant relationship with nurses’ attitudes toward the elderly care. Conclusion: Nurses’ attitudes toward the elderly care can be predicted by their moral intelligence, altruism and life satisfaction. Evaluation of these characteristics in nurses who provide services to the elderly can positively affect to their attitudes and prevent phenomena such as age discrimination.